2018
DOI: 10.1186/s13046-018-0706-6
|View full text |Cite
|
Sign up to set email alerts
|

Wilms’ tumor 1-associating protein promotes renal cell carcinoma proliferation by regulating CDK2 mRNA stability

Abstract: BackgroundWilms’ tumor 1-associating protein (WTAP) plays an important role in physiological processes and the development of tumor such as cell cycle regulation. The regulation of cell cycle is mainly dependent on cyclins and cyclin-dependent protein kinases (CDKs). Recent studies have shown that CDKs are closely related to the tumor diagnosis, progression and response to treatment. However, their specific biological roles and related mechanism in renal cell carcinoma (RCC) remain unknown.MethodsQuantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
114
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 29 publications
11
114
0
Order By: Relevance
“…Through enrichment analysis, these genes were found to up‐regulate the methylation of mRNA. Studies have found that m6A RNA modifications can affect tumour proliferation and patient prognosis through immunoregulatory effects . Our study also found that T regulatory cells (Treg) and CD4 memory‐activated T cells in patients with high WTAP expression were significantly lower than those in patients with low WTAP expression.…”
Section: Discussionsupporting
confidence: 65%
“…Through enrichment analysis, these genes were found to up‐regulate the methylation of mRNA. Studies have found that m6A RNA modifications can affect tumour proliferation and patient prognosis through immunoregulatory effects . Our study also found that T regulatory cells (Treg) and CD4 memory‐activated T cells in patients with high WTAP expression were significantly lower than those in patients with low WTAP expression.…”
Section: Discussionsupporting
confidence: 65%
“…Considering the opposite effect of ALKBH5 in different types of malignant tumors, more preclinical and clinical evidences are required to nd out the exact role of ALKBH5 in EAC. HNRNPA2B1, KIAA1429, WTAP, METTL16 were identi ed as protective genes, which was consistent with the results in many studies [44][45][46][47]. At present, the prognosis assessment mainly relies on TNM stage which includes limited risk factors [2].…”
Section: Discussionsupporting
confidence: 83%
“…In renal cell carcinoma, WTAP indicates poor survival of patients, and knockdown of WTAP impedes cell proliferation in vitro and tumorigenesis in vivo (56). Mechanistically, WTAP binds to 3 ′ -UTR of cyclin-dependent protein kinase 2 (CDK2) mRNAs and stabilizes the transcripts, lifting CDK2 protein level.…”
Section: Wtapmentioning
confidence: 99%